Physicians, Primary Caregivers and Topical Repellent: All Under-Utilised Resources in Stopping Dengue Virus Transmission in Affected Households - Simmons, Cameron (2018)
BACKGROUND: Primary health care facilities frequently manage dengue cases on an ambulatory basis for the duration of the patient's illness. There is a great opportunity for specific messaging, aimed to reduce dengue virus (DENV) transmission in and around the home, to be directly targeted toward this high-risk ambulatory patient group, as part of an integrated approach to dengue management. The extent however, to which physicians understand, and can themselves effectively communicate strategies to stop focal DENV transmission around an ambulatory dengue case is unknown; the matter of patient comprehension and recollection then ensues. In addition, the effectiveness of N,N-diethyl-3-methylbenzamide (DEET)-based insect repellent in protecting dengue patients from Aedes aegypti mosquitoes' bites has not been investigated. METHODOLOGY: A knowledge, attitude and practice (KAP) survey, focusing on the mechanisms of DENV transmission and prevention, was performed using semi-structured questionnaires. This survey was targeted towards the patients and family members providing supportive care, and physicians routinely involved in dengue patient management in Southern Vietnam. An additional clinical observational study was conducted to measure the efficacy of a widely-used 13% DEET-based insect repellent to repel Ae. aegypti mosquitoes from the forearms of dengue cases and matched healthy controls. PRINCIPAL FINDINGS: Among both the physician (n = 50) and patient (n = 49) groups there were several respondents lacking a coherent understanding of DENV transmission, leading to some inappropriate attitudes and inadequate acute preventive practices in the household. The application of insect repellent to protect patients and their relatives from mosquito bites was frequently recommended by majority of physicians (78%) participating in the survey. Nevertheless, our tested topical application of 13% DEET conferred only ~1hr median protection time from Ae. aegypti landing. This is notably shorter than that advertised on the manufacturer's label. No differences in landing time between febrile dengue cases or matched healthy controls (n = 19 experiments) were observed. CONCLUSION/SIGNIFICANCE: Our study identifies missed opportunities for primary care physicians to improve public health through communication of strategies that could prevent focal dengue transmission in and around a case household. We advocate better access to more efficient communication methods for physicians and auxilliary health workers, supporting to educate those at high risk of DENV transmission. Our empirical testing of a widely-available 13% DEET-based repellent was limited in its protective efficacy against Ae. aegypti mosquito bites, and therefore DENV transmission, suggesting more frequent application is necessary to be beneficial.